Tonic Stretch Reflex Threshold as a Measure of Ankle Plantar-Flexor Spasticity After Stroke. Issue 5 (1st May 2016) - Blanchette, Andreanne K.; Mullick, Aditi A.; Moïn-Darbari, Karina; Levin, Mindy F.
Abstract : Background: Commonly used spasticity scales assess the resistance felt by the evaluator during passive stretching. These scales, however, have questionable validity and reliability. The tonic stretch reflex threshold (TSRT), or the angle at which motoneuronal recruitment begins in the resting state, is a promising alternative for spasticity measurement. Previous studies showed that spasticity and voluntary motor deficits after stroke may be characterized by a limitation in the ability of the central nervous system to regulate the range of the TSRT. Objective: The study objective was to assess interevaluator reliability for TSRT plantar-flexor spasticity measurement. Design: This was an interevaluator reliability study. Methods: In 28 people after stroke, plantar-flexor spasticity was evaluated twice on the same day. Plantar-flexor muscles were stretched 20 times at different velocities assigned by a portable device. Plantar-flexor electromyographic signals and ankle angles were used to determine dynamic velocity-dependent thresholds. The TSRT was computed by extrapolating a regression line through dynamic velocity-dependent thresholds to the angular axis. Results: Mean TSRTs in evaluations 1 and 2 were 66.0 degrees (SD=13.1°) and 65.8 degrees (SD=14.1°), respectively, with no significant difference between them. The intraclass correlation coefficient (2, 1) was .851 (95% confidence interval=.703, .928). Limitations: The notion of dynamic stretch reflex threshold does not exclude the possibility that spasticity is dependent on acceleration, as well as on velocity; future work will study both possibilities. Conclusions: Tonic stretch reflex threshold interevaluator reliability for evaluating stroke-related plantar-flexor spasticity was very good. The TSRT is a reliable measure of spasticity. More information may be gained by combining the TSRT measurement with a measure of velocity-dependent resistance.